Mental health of medical students' during COVID-19 pandemic - Fedotova, Zoya (Psychosomatic Medicine and General Practice, 2023)
Introduction. The article focuses on the importance of studying the mental health of medical students. It specifically compares the mental well-being of domestic and foreign students, highlighting cultural and educational differences that impact their mental health. Given the COVID-19 pandemic, stress and anxiety levels among students, especially in the medical field, have increased, making this study highly relevant. The article proposes the development of a psychocorrection program to maintain and improve mental health using proven approaches and techniques adapted to medical education and student life. This program can be easily integrated into the educational process to effectively reduce psychological stress, prevent serious mental disorders and improve the mental health of students. Materials and methods. 185 higher education students were surveyed, including: 94 domestic students (main group) and 91 foreign students (comparison group). Both groups were from the Bogomolets National Medical University. The following methods were used in the study: ADNM-20, HADS, CSE, FPI, NSI, SF-36, CD-RISC, DERS. The following methods of statistical data processing were used in your work: descriptive statistics to summarize demographic and other basic characteristics of the groups, such as mean values (μ ± SD), percentages, and number of participants in each group. t-test for independent samples to compare the mean values between two groups of students (domestic and foreign) on different psychological scales. The Mann-Whitney U-test was also used to test for statistical differences between two independent groups when the data distribution did not follow a normal pattern. Pearson's correlation coefficient to analyze the relationships between different psychological and demographic variables in domestic and international students. Effect size analysis to assess the practical significance of the identified statistical differences between the groups. We have additionally performed a regression analysis. Results. Findings from recent research have shown that international students experience notably higher levels of stress, anxiety, and adaptation difficulties in comparison to their domestic counterparts. It is widely believed that these challenges are due, in large part, to the additional pressure of cultural adaptation and language barriers. To tackle this issue, a psychocorrection program has been proposed, with a specific focus on medical students. The program aims to use cognitive-behavioural interventions to enhance resilience and emotional regulation, with the ultimate goal of mitigating psychological distress and improving overall mental well-being.